The Influence of Asset Structure and Capital Structure on Return on Assets - Nicko Albart; Hadi Purnomo (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2024)
In a competitive business environment, PT. AirAsia Indonesia Tbk. faces challenges in enhancing financial performance through efficient asset structure management and capital structure. This study examines the impact of asset structure and capital structure on operational efficiency and profit performance of PT. AirAsia Indonesia Tbk. within a highly competitive business setting. The primary objective of this study is to understand the dynamics between financial structure, debt management, and operational efficiency in relation to the company's financial performance. Utilizing financial data from the years 2015 to 2023, this research applies path analysis to evaluate the influence of asset structure and capital structure on efficiency ratios and their subsequent impact on the company's profit performance. This study concludes that although there is a significant relationship between asset structure and capital structure with operational efficiency ratios, this relationship does not significantly affect the company's profit performance. These findings provide important insights for the management of PT. AirAsia Indonesia Tbk. in optimizing asset structure and capital structure to improve operational efficiency without a significant impact on enhancing profit performance.